ALK and IGF-1R as independent targets in crizotinib resistant lung cancer. Issue 1 (December 2017) - Wilson, Christabel; Nimick, Mhairi; Nehoff, Hayley; Ashton, John
Abstract ALK positive non-small cell lung cancer is highly responsive to ALK inhibitors such as crizotinib, but drug resistance typically develops within a year of treatment. In this study we investigated whether IGF-1R is an independent druggable target in ALK-positive lung cancer cells. We confirmed that combination ALK and IGF-1R inhibitor treatment is synergistically cytotoxic to ALK-positive lung cancer cells and that this remains the case for at least 12 days after initial exposure to crizotinib. ALK-positive cells with acquired resistance to crizotinib did not acquire cross-resistance to IGF-1R inhibition, though combination treatment in the resistant cells gave additive rather than synergistic cytotoxicity. We concluded that IGF-1R is an independent druggable target in ALK-positive lung cancer and support the trial of combination treatment.